Forest management contributes to climate mitigation by reducing fossil fuel consumption: A response to the letter by Welle et al. Issue 2 (16th October 2020) - Schulze, Ernst‐Detlef; Sierra, Carlos; Egenolf, Vincent; Woerdehoff, Rene; Irsinger, Roland; Baldamus, Conrad; Stupak, Inge; Spellmann, Hermann
Abstract : This is a Response to the Letter by Welle et al., 13, 286–287.